PENGARUH SHOPEE PAYLATER (SPAYLATER) DAN PROGRAM FLASH SALE TERHADAP PERILAKU KONSUMTIF MAHASISWA BERBELANJA DI APLIKASI SHOPEE (STUDI PADA MAHASISWA UNRI) - Sinaga, Ronaldo; Othman, Lie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this research is to determine and analyze the effect of SPaylater and the Flash Sale program on the consumptive behavior of UNRI students shopping on the Shopee application, either partially or simultaneously. The research method used is descriptive research with quantitative methods. The population in this study were UNRI students who were on the Bina Widya Campus. The sampling technique used is Non Probability Sampling. Samples are taken by means of purposive sampling and a sample of 104 students was obtained. The measurement scale used is the Likert Scale and data collection uses a questionnaire. Meanwhile, the analytical technique used is descriptive statistical method. The results of the study show that SPaylater has an influence on the consumptive behavior of UNRI students in shopping on the Shopee application. While the Flash Sale Program has no effect on the consumptive behavior of UNRI students in shopping on the Shopee application. Simultaneously SPaylater and the Flash Sale program have an effect on the consumptive behavior of UNRI students shopping on the Shopee application, so that the higher or lower the SPaylater and Flash Sale program provided by Shopee will still have an influence on the consumptive behavior of UNRI students. Keyword : spaylater, flash sale program, consumptive behavior, Shopee